PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maisaroh, Maisaroh; Yando, Agus Defri (LPPM Universitas Putera Batam, 2020)
He development of Greece in Indonesia can be seen with one of them being the increasing number of people investing in the capital market. The capital market in which the sale and purchase of shares occurs. qualitative. The population in the study were manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2014-2018 period. The method of determining the sample used is the PURPOSE SAMPLING method with several predetermined criteria, there are 8 sub-sector manufacturing companies. Research period for 2014-2018 or five (5) years. Testing the hypothesis in the study uses multiple linear regression analysis using the application of Statistical Package for Social Sciences (SPPS) version 20.0 as a commercial test tool. Keywords: Liquidity, Profitability, Leverage, Stock Price.